Comparative pericarp biomechanics and germination physiology of Raphanus raphanistrum and Raphanus pugioniformis indehiscent fruits - Steinbrecher, Tina; Bhattacharya, Samik; Binder, Jonathan; Kleemeier, Katharina; Przesdzink, Felix; Groene, Franziska; Jacoblinnert, Kyra; Mummenhoff, Klaus; Leubner-Metzger, Gerhard (Annals of botany, 2025)
BACKGROUND: The biomechanical, morphological and ecophysiological properties of plant seed/fruit structures are adaptations that support survival in unpredictable environments. High phenotypic variability of noxious and invasive weed species such as Raphanus raphanistrum (wild radish) allow diversification into new environmental niches. Dry indehiscent fruits (thick and lignified pericarp [fruit coat] enclosing seeds) have evolved many times independently. METHODS: A multiscale biomechanics and imaging (microscopy, X-ray, finite element stress simulation, puncture force analysis) approach was used to comparatively investigate the indehiscent fruits of R. raphanistrum (global weed), R. pugioniformis (endemic weed) and R. sativus (cultivated radish). RESULTS: The hard pericarp of Raphanus species (Brassicaceae) imposes mechanical dormancy by preventing full phase-II water uptake of the enclosed seeds. The apparently unilocular fruits of Raphanus species develop from two fused valves, pericarp rupture to permit germination is confined to the midvalve regions, and each midvalve region contains a predetermined breaking zone that is biomechanically defined by the internal shape of the seed chambers. Direct biomechanical analysis revealed great variability in within-fruit and between-fruits pericarp resistances. CONCLUSIONS: Variability in pericarp-imposed dormancy provides a bet-hedging strategy to affect soil seed bank persistence and prolong the germinability period.
Keywords: Raphanus; finite element stress simulation; biomechanika; predetermined breaking zone; klíčení; analýza metodou konečných prvků; Finite Element Analysis; pericarp-imposed mechanical dormancy; semena rostlinná; ovoce; Germination; Fruit; soil seed bank persistence; fruit coat biomechanics; Biomechanical Phenomena; Functional morphology; Seeds